### Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation : 5*x-x^2-(6)=0## Step by step solution :

## Step 1 :

## Step 2 :

Pulling out like terms :2.1 Pull out like factors:-x2 + 5x - 6=-1•(x2 - 5x + 6)

Trying to factor by splitting the middle term2.2Factoring x2 - 5x + 6 The first term is, x2 its coefficient is 1.The middle term is, -5x its coefficient is -5.The last term, "the constant", is +6Step-1 : Multiply the coefficient of the first term by the constant 1•6=6Step-2 : Find two factors of 6 whose sum equals the coefficient of the middle term, which is -5.

-6 | + | -1 | = | -7 | ||

-3 | + | -2 | = | -5 | That"s it |

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step2above, -3 and -2x2 - 3x-2x - 6Step-4 : Add up the first 2 terms, pulling out like factors:x•(x-3) Add up the last 2 terms, pulling out common factors:2•(x-3) Step-5:Add up the four terms of step4:(x-2)•(x-3)Which is the desired factorization

Equation at the end of step 2 :(2 - x) • (x - 3) = 0

## Step 3 :

Theory - Roots of a product :3.1 A product of several terms equals zero.When a product of two or more terms equals zero, then at least one of the terms must be zero.We shall now solve each term = 0 separatelyIn other words, we are going to solve as many equations as there are terms in the productAny solution of term = 0 solves product = 0 as well.Solving a Single Variable Equation:3.2Solve:-x+2 = 0Subtract 2 from both sides of the equation:-x = -2 Multiply both sides of the equation by (-1) : x = 2

Solving a Single Variable Equation:3.3Solve:x-3 = 0Add 3 to both sides of the equation:x = 3

### Supplement : Solving Quadratic Equation Directly

Solving x2-5x+6 = 0 directly Earlier we factored this polynomial by splitting the middle term. let us now solve the equation by Completing The Square and by using the Quadratic FormulaParabola, Finding the Vertex:4.1Find the Vertex ofy = x2-5x+6Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up and accordingly has a lowest point (AKA absolute minimum).We know this even before plotting "y" because the coefficient of the first term,1, is positive (greater than zero).Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is given by -B/(2A). In our case the x coordinate is 2.5000Plugging into the parabola formula 2.5000 for x we can calculate the y-coordinate:y = 1.0 * 2.50 * 2.50 - 5.0 * 2.50 + 6.0 or y = -0.250

Parabola, Graphing Vertex and X-Intercepts :Root plot for : y = x2-5x+6 Axis of Symmetry (dashed) {x}={ 2.50} Vertex at {x,y} = { 2.50,-0.25} x-Intercepts (Roots) : Root 1 at {x,y} = { 2.00, 0.00} Root 2 at {x,y} = { 3.00, 0.00}

Solve Quadratic Equation by Completing The Square4.2Solvingx2-5x+6 = 0 by Completing The Square.Subtract 6 from both side of the equation :x2-5x = -6Now the clever bit: Take the coefficient of x, which is 5, divide by two, giving 5/2, and finally square it giving 25/4Add 25/4 to both sides of the equation :On the right hand side we have:-6+25/4or, (-6/1)+(25/4)The common denominator of the two fractions is 4Adding (-24/4)+(25/4) gives 1/4So adding to both sides we finally get:x2-5x+(25/4) = 1/4Adding 25/4 has completed the left hand side into a perfect square :x2-5x+(25/4)=(x-(5/2))•(x-(5/2))=(x-(5/2))2 Things which are equal to the same thing are also equal to one another.

You are watching: 5x + x² > 100, then x is not

See more: Which Of The Following Is True Of Sole Proprietorships And Corporations?

Sincex2-5x+(25/4) = 1/4 andx2-5x+(25/4) = (x-(5/2))2 then, according to the law of transitivity,(x-(5/2))2 = 1/4We"ll refer to this Equation as Eq. #4.2.1 The Square Root Principle says that When two things are equal, their square roots are equal.Note that the square root of(x-(5/2))2 is(x-(5/2))2/2=(x-(5/2))1=x-(5/2)Now, applying the Square Root Principle to Eq.#4.2.1 we get:x-(5/2)= √ 1/4 Add 5/2 to both sides to obtain:x = 5/2 + √ 1/4 Since a square root has two values, one positive and the other negativex2 - 5x + 6 = 0has two solutions:x = 5/2 + √ 1/4 orx = 5/2 - √ 1/4 Note that √ 1/4 can be written as√1 / √4which is 1 / 2

### Solve Quadratic Equation using the Quadratic Formula

4.3Solvingx2-5x+6 = 0 by the Quadratic Formula.According to the Quadratic Formula,x, the solution forAx2+Bx+C= 0 , where A, B and C are numbers, often called coefficients, is given by :-B± √B2-4ACx = ————————2A In our case,A= 1B= -5C= 6 Accordingly,B2-4AC=25 - 24 =1Applying the quadratic formula : 5 ± √ 1 x=————2So now we are looking at:x=(5±1)/2Two real solutions:x =(5+√1)/2= 3.000 or:x =(5-√1)/2= 2.000